The Influence of Self-Confidence, Training, and Employee Relations on Employee Performance (A Study at PT. Yakjin Jaya Indonesia II Sukabumi) - Rahayu M.F, Neng Nova Sri; Mulia Z, Faizal; Nurmala, Resa (Universitas Muhammadiyah Pontianak, 2025)
This study investigates the influence of self-confidence, training, and employee relations on employee performance at PT. Yakjin Jaya Indonesia II Sukabumi. A quantitative approach using descriptive and associative methods was applied, with data collected from 292 employees selected through simple random sampling. Analysis was conducted using multiple linear regression via SPSS 27. The results show that all three independent variables significantly and positively affect employee performance both simultaneously and partially. The coefficient of determination indicates that these variables account for 58.9% of the variance in performance. These findings highlight the importance of psychological empowerment, technical training, and harmonious workplace relationships in enhancing company productivity.